BRIEF OVERVIEW ON HEPATITIS C VIRUS IMMUNOASSAYS - Sharma, Rajesh; Sharma, Pankaj; Talat, Gaush; Gautam, Praveen; Chhabra, Reba; Singh, Surinder (International Journal of Research -GRANTHAALAYAH, 2016)
The publication deals with a brief overview of Hepatitis C Virus (HCV) and donor blood screening for HCV by using conventional Rapid, Enzyme Linked Immunosorbent Assay (ELISA) and Chemiluminescence Immunoassay (CLIA) also. The advantages of various generation of HCV tests in terms of sensitivity, specificity and reduction in window period are discussed.